2014
DOI: 10.1007/s00395-014-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-144 is a circulating effector of remote ischemic preconditioning

Abstract: Remote ischemic preconditioning (rIPC) induced by cycles of transient limb ischemia and reperfusion is a powerful cardioprotective strategy with additional pleiotropic effects. However, our understanding of its underlying mediators and mechanisms remains incomplete. We examined the role of miR-144 in the cardioprotection induced by rIPC. Microarray studies first established that rIPC increases, and IR injury decreases miR-144 levels in mouse myocardium, the latter being rescued by both rIPC and intravenous adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 48 publications
4
179
0
2
Order By: Relevance
“…267 Several different micro RNAs have been identified in protocols of IPC, [268][269][270][271][272] POC, 270,[272][273][274][275] and RIC 270,[276][277][278] in various species, including humans. 276,277 Unless the microarray screening data were confirmed by RT-PCR, 269,270,272,275,277 it is difficult to decide whether the identified microRNAs reflect robust data or circumstantial epiphenomena.…”
Section: Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…267 Several different micro RNAs have been identified in protocols of IPC, [268][269][270][271][272] POC, 270,[272][273][274][275] and RIC 270,[276][277][278] in various species, including humans. 276,277 Unless the microarray screening data were confirmed by RT-PCR, 269,270,272,275,277 it is difficult to decide whether the identified microRNAs reflect robust data or circumstantial epiphenomena.…”
Section: Micrornasmentioning
confidence: 99%
“…267 Several different micro RNAs have been identified in protocols of IPC, [268][269][270][271][272] POC, 270,[272][273][274][275] and RIC 270,[276][277][278] in various species, including humans. 276,277 Unless the microarray screening data were confirmed by RT-PCR, 269,270,272,275,277 it is difficult to decide whether the identified microRNAs reflect robust data or circumstantial epiphenomena. Likewise, unless the identified microRNAs were demonstrated to be causally related to the expression/activity of an established cardioprotective protein 268,270,274 or, even better, to IS reduction, for example, by abrogation of IS reduction by an antagonist 269,271,273,276 to an increased microRNA or exogenous administration of a decreased microRNA, 268,272 respectively, the functional relevance of the reported microRNA in cardioprotective signaling must remain unclear.…”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…or myocyte hypertrophic signals, or even by delivery from distant sites, as found in remote preconditioning 144,145 . In addition to exosomes, tunnelling nanotubes -long, intercellular connections of 50-700 nm in diameter prov iding membrane continuity between connected cells -have emerged as an alternative means of transfer of microRNAs and even organelles 146,147 .…”
Section: Nature Reviews | Cardiologymentioning
confidence: 99%
“…Li et al (67) reported that remote ischemic preconditioning, to the opposite of IR injury, increased miR-144 levels in mouse myocardium and miR-144 precursor in exosomes. Systemic treatment with miR-144 increased P-Akt, P-GSK3β and P-p44/42 MAPK, and induced early and delayed cardioprotection resulting in improved functional recovery and decreased infarct size similar to that achieved by remote ischemic preconditioning.…”
Section: Exosomes Mediate Remote Ischemic Preconditioningmentioning
confidence: 99%